The Spectral Analysis and Application of Low-degree Modified Spheroidal Hotine Kernel - MA Jian,WEI Ziqing,REN Hongfei (Journal of Geodesy and Geoinformation Science, 2020)
The traditional spheroidal kernel results in the spectrum leakage, and the utilization rate of the removed degrees of the measured data is low. Hence, a kind of spheroidal kernel whose high- and low-degrees are both modified is introduced in this research, which is exampled by the Hotine kernel. In addition, the low-degree modified spheroidal kernel is proposed. Either cosine or linear modification factors can be utilized. The modified kernel functions can effectively control the spectrum leakage compared with the traditional spheroidal kernel. Furthermore, the modified kernel augments the contribution rate of the measured data to height anomaly in the modified frequency domain. The experimental results show that the accuracy of the quasi-geoid by the cosine or linear low-degree modified kernel is higher than that by the traditional spheroidal kernel. And the accuracy equals the accuracy of the quasi-geoid using the spheroidal kernel with high- and low-degrees modified approximately when the low-degree modification bandwidths of these two kinds of kernels are the same. Since the computational efficiency of the low-degree modified kernel is much higher, the low-degree modified kernel behaves better in constructing the (quasi-) geoid based on Stokes-Helmert or Hotine-Helmert boundary-value theory.